Farmakovijilans ve psikofarmakolojideki önemi - (:unkn) unknown (My University, 2009)
İlaçlar doğru kullanılmasına rağmen advers etkilere neden olabildiklerinden, ilaçların pazarlama sonrası da izlenmeleri gereklidir. Advers ilaç etkisi, ilacın kullanımına bağlı olarak veya başka ilaçlarla beraber kullanılması sonucu normal koşullarda meydana gelen istenmeyen veya zararlı etkilerdir. Advers ilaç reaksiyonları genetik polimorfizm, farmakokinetik ve farmakodinamik faktörler de dahil olmak üzere bireysel farklılıklar nedeniyle oluşabilmektedir. Psikotrop ilaçlarla ilgili advers etki bildirimleri giderek artmaktadır. İlaçların neden olduğu depresyon, psikoz, mani ve konfüzyon gibi psikiyatrik sorunlar sıklıkla görülebilir. Bazen de bir psikotrop ile bir diğer psikotropun veya başka ilaç gruplarının kombinasyonları sonucu advers reaksiyonlar gelişebilmektedir. Buna örnek olarak, antidepresan tedavi sırasında libido azalması başta olmak üzere cinsel işlev bozuklukları, çeşitli dermatolojik, kardiyovasküler, hematolojik ve nörolojik advers etkiler gösterilebilir. Trisiklik antidepresan (TSA)la, bazen de seçici serotonin gerialım inhibitörleri (SSGİ) ile yapılan kombinasyonların serotonin sendromuna neden olabileceği gösterilmiştir. Monoaminoksidaz inhibitörleri (MAOİ), TSA ve paroksetin, venlafaksin gibi bazı yeni antidepresanların birden kesilmesi ise yoksunluk tablosu oluşturabilir. Bildirimler yeni kuşak antipsikotik kullanımına bağlı olarak diyabet, serum leptin düzeylerinde artma, insülin direnci, lipid profili üzerine olumsuz etkiler, anjiyoödem ve kardiyovasküler hastalık riskinin artabileceğini göstermiştir. Psikotroplara bağlı advers ilaç etkilerinin bildirilebileceği tarafsız kuruluşların oluşturulması, dolayısıyla advers etki bildirimlerinin düzenli olarak izlenmesi tüm dünyada çok önem verilen bir konu haline gelmiştir. Bu bağlamda Türkiyede farmakovijilans konusunda 1985 yılından beri T.C. Sağlık Bakanlığına bağlı olarak Türk İlaç Advers Etkilerini İzleme ve Değerlendirme Merkezinde (TÜFAM) faaliyetlerini sürdürülmektedir. Advers ilaç etkileri ile ilgili olarak biz sağlık profesyonellerine düşen görev, karşılaşılan advers olayları hiç vakit geçirmeden TÜFAMa bildirmenin yanında, literatüre de kazandırarak dünyadaki tüm meslektaşlarımızı bilgilendirmek ve böylece bu alandaki farkındalığımızı artırmaktır

Drugs may cause adverse effects even they are used correctly. Therefore, drugs need to be monitored during postmarketing period. An adverse drug reaction is an unwanted or harmful reaction experienced after the administration of a drug due to use of a drug or suspected relation to the use of drug or use of a drug in combination with other drugs under normal conditions. Adverse drug reactions can sometimes occur due to individual differences including genetic polymorphism and pharmacokinetic and pharmacodynamic factors. Adverse effect reporting has been increasing. Drug-induced mental health problems, which occur somewhat commonly, include depression, psychosis, mania, and confusion. Sometimes psychotropic drugs or their combinations with other drugs can result in adverse reactions. It has been demonstrated that sexual side effects, especially decreased libido were the most frequent adverse effects during antidepressant treatment. Others included various dermatological, cardiovascular, hemotological, and neurological reactions. Serotonin reuptake inhibitors (SSRI) can cause bleeding and the risk may increase more in case of combination with non-steroidal antiinşammatory (NSAI) drugs. The combinations mostly with trycyclic antidepressants (TCA) and sometimes with SSRI may result in serotonin syndrome. A withdrawal syndrome can occur when Monoamine oxidase inhibitor (MAOI) drugs and tricyclic antidepressants are stopped suddenly. Reports have revealed that diabetes, increase in serum leptin, insulin resistance, negative effects on lipid profile, angioedema, and cardiovascular disease risk incidences have been higher in patients treated with new generation antipsychotics. Healthcare professionals have an important role to play in preventing adverse reactions due to prescribed or over-the-counter medicines. Establishing unbiased organizations to monitor adverse drug effects of drugs and receive reports of adverse effect notices on a scheduled basis have been an important issue world- wide. In this regard, TUFAM (Turkish Center for Monitoring and Evaluating Adverse Drug Effects), a unit of Turkish Ministry of Health, was established and has been in operation since 1985 in the field of pharmacovigilance. On the adverse drug effects issue, we the healthcare professionals should report the noticed adverse effect incidences promptly to TUFAM. In addition we should share our experiences with global healthcare community by writing and submitting case reports and articles to scientific periodicals.
Pharmacovigilance and its significance in psychopharmacology
Keywords: Farmakoloji ve Eczacılık